Perbedaan Model Teaching Personal Social Responsibility (TPSR) dan Cooperative Learning Untuk Mengembangkan Toleransi dan Tanggun Jawab Siswa - Dupri Dupri; Alfi Candra; Novia Nazirun (Universitas Pendidikan Indonesia, 2019)
This research was motivated by the decline of the students’ responsibility and tolerance at school. This condition is characterized by the high rate of juvenile delinquency, brawls among students, and the influence of technology that decreases the students’ interaction with their surroundings, community, and other students at school. This study revealed the differences between TPSR model and cooperative learning models in increasing students' responsibility and tolerance in physical education learning. The difference was found on students in the urban and rural area. The method used in this study was Quasi Experimental study with the pretest post-test two treatment design. The population of this study were 192 students. The sampling technique used Cluster Random Sampling technique so that the sample of this study were 128 students. The two different treatment models namely the TPSR models and cooperative learning models were conducted. The instrument used was a responsibility and tolerance questionnaire analyzed by multivariate analysis (Manova). The results of this study found that cooperative learning model is better in developing responsibilities, while the Teaching Personal Social Responsibility (TPSR) model is better for developing students' tolerance in physical education learning. Both of these models can be used in physical education learning to build character and active learning process. AbstrakPenelitian ini dilatar belakangi atas dasar sudah menurunnya sikap tanggung jawab dan toleransi siswa disekolah, kondisi ini ditandai oleh tingginya angka kenakalan remaja, tawuran antar siswa dan lebih lagi pengaruh teknologi yang begitu kuat membuat siswa jarang bersosialisasi dengan masyarakat sekitar dan sesama siswa disekolah. Penelitian ini mengungkapkan perbedaan Model TPSR dengan model kooperatif dalam meningkatkan sikap tanggung jawab dan toleransi siswa dalam pembelajaran penjas serta juga dibedakan antara siswa di daerah dengan siswa yang sekolah dikota. Metode yang digunakan dalam penelitian ini adalah quasi eksperimen dengan desain the pretest post-test two treatment design. Populasi penelitian ini berjumlah 192, untuk memperoleh sampel pada penelitian ini teknik pengambilan sampel mengunakan teknik Cluster Random Sampling sehingga diperolah sampel penelitian ini berjumlah 128. Perlakuannya pada dua model yang berbeda yaitu model TPSR dan model kooperatif. Instrument yang digunakan adalah angket tanggung jawab dan toleransi, analisis dengan multivarian (MANOVA). Hasil penlitian ini menemukan bahwa Model kooperatif lebih mampu mengembangkan tanggung jawab sedangkan model TPSR dalam sikap toleransi siswa pada pembelajaran pendidikan jasmani. Kedua model ini bisa dijadikan sebagai model pembelajaran pendidikan jasmani yang menanamkan karakter dan keaktifan dalam menjalankan proses belajar.